2018
DOI: 10.3390/foods7040045
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Physical Post-Harvest Treatments for Shelf-Life Extension of Cereal Crops

Abstract: As a result of the rapidly growing global population and limited agricultural area, sufficient supply of cereals for food and animal feed has become increasingly challenging. Consequently, it is essential to reduce pre- and post-harvest crop losses. Extensive research, featuring several physical treatments, has been conducted to improve cereal post-harvest preservation, leading to increased food safety and sustainability. Various pests can lead to post-harvest losses and grain quality deterioration. Microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 93 publications
(126 reference statements)
1
50
0
1
Order By: Relevance
“…Results of the HTS analysis indicated that fumigation of the grains with phosphine had a significant effect on the diversity and abundance of various components of the wheat-grain microbiome. It is known that many other factors could affect the stored seed microbial community such as temperature, humidity, water activity, grain moisture (Schmidt et al, 2018). Nevertheless, in the current study, the impact of such environmental factors was minor due to the optimal and stable weather conditions during a 6-months storage period.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the HTS analysis indicated that fumigation of the grains with phosphine had a significant effect on the diversity and abundance of various components of the wheat-grain microbiome. It is known that many other factors could affect the stored seed microbial community such as temperature, humidity, water activity, grain moisture (Schmidt et al, 2018). Nevertheless, in the current study, the impact of such environmental factors was minor due to the optimal and stable weather conditions during a 6-months storage period.…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxin contamination could further occur during the processing of rice grains [4]. Additionally, a delayed drying process and excess moisture (above 13%) [5] can promote the growth of fungi. Numerous species in Aspergillus section Flavi are common in plants and their processed derivatives, with some producing diverse mycotoxins, such as aflatoxins, 3-nitropropionic acid, tenuazonic acid, and cyclopiazonic acid [6].…”
Section: Introductionmentioning
confidence: 99%
“…Whole millet samples demonstrated a no increase trend in the fungal growth from 0 to 90 days in the heat and γ‐irradiated samples at 2.50 kGy. Similarly, a study highlighted the combination of time and temperature to reduce the fungal count for 15 days at 60°C, 5 days at 70°C, and 2 days at 80°C (Schmidt et al., 2018).…”
Section: Resultsmentioning
confidence: 99%